The problems and promise of commercial society : Adam Smith's response to Rousseau - Rasmussen, Dennis C. (Dennis Carl), 1978- (Pennsylvania State University Press, 2008)
Adam Smith is popularly regarded as the ideological forefather of laissez-faire capitalism, while Rousseau is seen as the passionate advocate of the life of virtue in small, harmonious communities and as a sharp critic of the ills of commercial society. But, in fact, Smith had many of the same worries about commercial society that Rousseau did and was strongly influenced by his critique. In this first book-length comparative study of these leading eighteenth-century thinkers, Dennis Rasmussen highlights Smith's sympathy with Rousseau's concerns and analyzes in depth the ways in which Smith crafted his arguments to defend commercial society against these charges. These arguments, Rasmussen emphasizes, were pragmatic in nature, not ideological: it was Smith's view that, all things considered, commercial society offered more benefits than the alternatives. Just because of this pragmatic orientation, Smith's approach can be useful to us in assessing the pros and cons of commercial society today and thus contributes to a debate that is too much dominated by both dogmatic critics and doctrinaire champions of our modern commercial society.